Camptodactyly: early nonoperative treatment - G. Pajardi; C. Parolo; G. Proserpio; V. Ponti; P. Rossi; C. Cargnelutti (PAGEPress Publications, 2013)
Purpose: To analyse the classifications and the conservative protocols used by hand surgery operative's units and published in the last 15 years. To draw a comparison between those classifications and protocols and the ones used in our unit. Material and Methods: The published conservative treatments have been analysed and then our protocol has been described through the analysis of three cases currently treated in our division. Results: It has been highlighted that camptodactyly classifications are not homogeneous. Moreover, in conservative treatment, different typology and posology of splints have been adopted. Our unit uses the Foucher's classification to define the type of splint that it is necessary. Conclusions: Despite the authors choose different types of splint, they agree that in the most cases of camptodactily the initial approach is conservative. In our unit static and dynamic splints are made directly on the patient's hand and they are monitored with goniometrical measurements, obtaining great results.